2005
DOI: 10.1111/j.1365-3040.2005.01414.x
|View full text |Cite
|
Sign up to set email alerts
|

Heat sensitivity of photosynthetic electron transport varies during the day due to changes in sugars and osmotic potential

Abstract: In water-stressed leaves, accumulation of neutral osmotica enhances the heat tolerance of photosynthetic electron transport. There are large diurnal and day-to-day changes in leaf sugar content because of variations in net photosynthetic production, respiration and retranslocation. To test the hypothesis that diurnal and day-to-day variations in leaf sugar content and osmotic potential significantly modify the responses to temperature of photosynthetic electron transport rate, we studied chlorophyll fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 81 publications
(167 reference statements)
4
86
1
Order By: Relevance
“…It was also suggested that increased allocation to the NSC pool may be a general response to stress, indicating more severe carbon limitation to growth, rather than vice versa (Wiley and Helliker 2012). Further, high soluble sugar concentrations in the leaves may improve their ability to photosynthesise at high temperatures (Hüve et al 2006). If these assertions are correct, there may not be a direct negative relationship between the size of the NSC pool and the ability of tropical trees and lianas to increase growth in response to elevated c a .…”
Section: Effects Of Elevated C a On Growthmentioning
confidence: 99%
“…It was also suggested that increased allocation to the NSC pool may be a general response to stress, indicating more severe carbon limitation to growth, rather than vice versa (Wiley and Helliker 2012). Further, high soluble sugar concentrations in the leaves may improve their ability to photosynthesise at high temperatures (Hüve et al 2006). If these assertions are correct, there may not be a direct negative relationship between the size of the NSC pool and the ability of tropical trees and lianas to increase growth in response to elevated c a .…”
Section: Effects Of Elevated C a On Growthmentioning
confidence: 99%
“…There is a large variation in temperature responses of photosynthesis both within and among species, as well as significant daily and seasonal variations Niinemets et al 1999;Medlyn et al 2002a, b;Hüve et al 2006;Kattge and Knorr 2007). Over the short term, such as rapid temperature fluctuations during the day, changes in temperature dependence of photosynthesis may result from alterations in the CO 2 concentration at the carboxylation site and modifications in the rate of ribulose-1,5-bisphosphate (RuBP) carboxylation by Rubisco and RuBP regeneration (Medlyn et al 2002a, b;Kattge and Knorr 2007).…”
Section: Introductionmentioning
confidence: 98%
“…T c can be influenced by a series of environmental parameters like ambient temperature (Dreyer et al, 2001;Havaux, 1993;Robakowski et al, 2002), water availability (Epron, 1997a;Havaux, 1992;Ladjal et al, 2000) and plant growth regulators like ABA (Havaux, 1992;Ivanov et al, 1992). T c varies largely with season, in parallel to ambient temperatures, and increases during summer and decreases during autumn (Froux et al, 2004;Hüve et al, 2006). Large increases of T c can be induced by increasing ambient temperatures over a few days as shown in silver fir (Robakowski et al, 2002).…”
Section: Introductionmentioning
confidence: 99%